Fertility postponement and regional patterns of dispersion in age at first birth: Descriptive findings and interpretations - Mathías Nathan; Ignacio Pardo (Comparative Population Studies (CPoS), 2019)
Previous studies have documented an increasing heterogeneity in first-birth timing in countries experiencing the postponement transition. Sobotka (2004), for instance, showed a rising dispersion in age at first birth in developed countries, particularly in the United Kingdom and the United States, where the timing polarisation between more and less advantaged women is most evident. However, these studies have included few countries outside Europe and North America, and lack a thorough interpretation of the rising dispersion in first births. Our aim is to compare the evolution of dispersion in age at first birth in countries in Europe, East Asia, North America and South America. Using data from the Human Fertility Database and the Human Fertility Collection, we describe the evolution of the period mean age at first birth and its variance for 21 countries since 1970. In line with previous studies, our results show a widespread pattern of increasing heterogeneity in age at first birth after the onset of the postponement transition, although with marked differences among regions and countries. The greatest heterogeneity can be found in countries where timing of family formation varies greatly among women with different socioeconomic status. Chile and Uruguay, in particular, exhibit the highest heterogeneity even though they are at the beginning of the postponement transition. There is no general explanation of why dispersion increased as the mean age at first birth rose. Further studies in this area should investigate causes and interpretations of this trend, and develop measures for studying heterogeneity in fertility timing.
urn:nbn:de:bib-cpos-2019-07en4
Keywords: 300; Fertility; Fertility postponement; Dispersion in age at first birth; Age-specific fertility rates